SOCIO-ECONOMIC CONSEQUENCES OF DIGITAL ECONOMY DEVELOPMENT (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The digital economy is an important factor in the development of the economy and society as a whole. It has both positive and negative consequences, which must be taken into account when developing regulatory measures and social support.